Symbols and their information, communication and organizational functions - Turzhan, О.І. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
One of the most effective and fastest ways to convey information in the information age is the use of symbols. The effectiveness of visual symbols is especially evident over time. Because today’s audience is well adapted to the perception of visual information. This is facilitated by the Internet and various digital technologies. Thanks to these features, the use of symbols has increased both in the dissemination of information and at any organizational event. Information, communication and organizational functions of symbols have been conducted since ancient times. It is still relevant because of its positive impact on communication, ease of use, and effectiveness. This research article provides a scientific and theoretical analysis of the main aspects of the modern information, communication and organizational function of symbols on the basis of previous studies, which examined the main features of symbols. There was also a scientific analysis of the factors associated with the conventional medical mask during the pandemic that began this year, as a symbol of organizational, information and communication functions.The importance of public relations is scientifically assessed and categories of influence of visual symbols are analyzed.